2000
DOI: 10.1054/bjoc.2000.1269
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aromatase activity and expression in MCF-7 cells by the chemopreventive retinoid N -(4-hydroxy-phenyl)-retinamide

Abstract: SummaryThe effect of the chemopreventive synthetic retinoid N-(4-hydroxyphenyl)-retinamide (4-HPR) on aromatase activity and expression was examined. 4-HPR caused a dose-dependent inhibition of aromatase activity in microsomes isolated from JEG-3 human placental carcinoma cells. The kinetics of inhibition were analysed by double-reciprocal plot. The Km of the substrate increased and the Vmax of the reaction decreased in the presence of 4-HPR, indicating that enzyme inhibition involved both competition for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The effect of the chemopreventive synthetic retinoid 4-HPR on aromatase activity inhibition in microsomes of JEG3 cells and in MCF-7 cells has been shown previously (41). Because VN/14-1 also possesses retinoidal properties and, in addition, also inhibits retinoic acid metabolism by blocking CYP-mediated catabolism of ATRA, we investigated its effect on CYP-19 (aromatase) activity.…”
Section: Resultsmentioning
confidence: 90%
“…The effect of the chemopreventive synthetic retinoid 4-HPR on aromatase activity inhibition in microsomes of JEG3 cells and in MCF-7 cells has been shown previously (41). Because VN/14-1 also possesses retinoidal properties and, in addition, also inhibits retinoic acid metabolism by blocking CYP-mediated catabolism of ATRA, we investigated its effect on CYP-19 (aromatase) activity.…”
Section: Resultsmentioning
confidence: 90%
“…As a result, there is a recognized need for next generation inhibitors [23]. A large number of investigators have invested significant effort in the search for novel structures [24][25][26][27] and mechanisms [28][29][30] that bring about adequate aromatase inhibition, while limiting side effects. This search remains active.…”
Section: Introductionmentioning
confidence: 99%
“…We [31] and others [32,33] previously demonstrated that the synthetic retinoid 4-hydroxyphenylretinamide (4-HPR) inhibits the activity of aromatase in vitro. However, despite the established chemopreventive effect of retinoids towards breast cancer, and the crucial role of aromatase in the growth of estrogen-dependent tumors, the effects of ROH and other naturally occurring retinoids on aromatase activity have not, to the best of our knowledge, been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Therefore we examined the kinetics of enzyme inhibition using a double-reciprocal plot and found that ROH, like 4-HPR [31], involved both competition for the substrate binding site and noncompetitive components (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%